Passengers' acceptance and perceptions of risk while riding in an automated vehicle on open, public roads. (November 2021) - Pascale, Michael T.; Rodwell, David; Coughlan, Pete; Kaye, Sherrie-Anne; Demmel, Sébastien; Dehkordi, Sepehr Ghasemi; Bond, Andy; Lewis, Ioni; Rakotonirainy, Andry; Glaser, Sébastien
Highlights: Conducted with public participants on open, public roads in uncontrolled traffic. Acceptance increased and perceptions of risky vehicle behaviors decreased. Changes in perceived risk were greater than changes in acceptance. Passengers in the front seat may experience automated driving differently. Frequent false hazards (FH) may be experienced positively than trips with fewer FH. Abstract: Automated vehicles are an emerging technology that operate with differing levels of automatic control (SAE levels). The current study explored participants' acceptance of a conditional (Level 3) automated vehicle (AV) before and after riding as a passenger for 10 min on open, public roads in uncontrolled traffic. Additionally, participants were asked to rate the riskiness (perceived risk) of a variety of vehicle maneuvers, such as turning, accelerating, and braking when approaching an intersection. We predicted that participants would report higher acceptance ratings and lower perceived risk ratings after experiencing the AV compared to pre-trip ratings. Further, we predicted that participants riding in the front-passenger seat would report higher ratings for risk compared to participants sitting in the rear-passenger or rear-driver seats. Sixty participants from South-East Queensland, Australia (aged 21–82 years; M age = 45.78; 23 female) took part in the study. Compared to pre-trip responses, participants reported statistically higher ratings for acceptance, as well as statistically lower ratings for perceived risk with respect to specific vehicle maneuvers performed while in automated mode. Differences were detected between seats for perceived risk, but these results were less clear. Increases in acceptance and decreases in risk were also detected as the number of false hazards detected by the vehicle increased. Overall, these findings suggest that acceptance towards AVs may increase, and expectations of risk related to AV maneuvers may decrease, after participants have experienced the vehicles firsthand, on an open, public road in an uncontrolled traffic environment.